Markers of Inflammation (IL-4, IL-6, IL-8, IL-10) in Induced Sputum of Children with Bronchitis - O.S. Lupaltsova; G.S. Senatorova (Zaslavsky O.Yu., 2013)
The paper presents the results of investigations of the immune system in children with bronchitis. Factors of poor prognosis and transformation of bronchitis in chronic bronchopulmonary pathology were detected, including violations of cytokine production. In a study the conditions of persistence of bronchopulmonary inflammation were established by studying the concentration of cytokines in induced sputum of 38 children with acute bronchitis, in 35 children with pneumonia, in 15 children with chronic bronchopulmonary pathology and pneumofibrosis and in 18 healthy children. When compared with the indices of control group, in patients of all investigated groups significantly elevated levels of interleukins (IL-4, IL-6, IL-8, IL-10) in induced sputum were observed. Increase in concentration of IL-8 and IL-10 in induced sputum of children with bronchitis and pneumonia can be considered as a risk factor for developing chronic bronchopulmonary disease.